Performance-Enhanced Textured Silicon Solar Cells Based on Plasmonic Light Scattering Using Silver and Indium Nanoparticles - Wen-Jeng Ho (Materials, 2015)
Performances of textured crystalline-silicon (c-Si) solar cells enhanced by silver nanoparticles (Ag-NPs) and indium nanoparticles (In-NPs) plasmonic effects are experimentally demonstrated and compared. Plasmonic nanoparticles integrated into textured c-Si solar cells can further increase the absorption and enhance the short-circuit current density (Jsc) of the solar cell. To examine the profile of the proposed metallic particles, the average diameter and coverage of the In-NPs (Ag-NPs) at 17.7 nm (19.07 nm) and 30.5% (35.1%), respectively, were obtained using scanning electron microscopy. Optical reflectance and external quantum efficiency response were used to measure plasmonic light scattering at various wavelengths. Compared to a bare reference cell, the application of In-NPs increased the Jsc of the cells by 8.64% (from 30.32 to 32.94 mA/cm2), whereas the application of Ag-NPs led to an increase of 4.71% (from 30.32 to 31.75 mA/cm2). The conversion efficiency of cells with embedded In-NPs (14.85%) exceeded that of cells with embedded Ag-NPs (14.32%), which can be attributed to the broadband plasmonic light scattering of the In-NPs.